Performance of cows in the lactation following rbST treatment - James R. Dunham (Kansas Agricultural Experiment Station Research Reports, 1995)
The first 305-2x-ME lactation record (after 45 days in milk) projected by the DHI program in 28 cows was not different from their first projected lactation record in a previous lactation in which recombinant bovine somatotropin (rbST) injections were begun by the 90th day of lactation. These results suggest when rbSTtreated cows are fed and managed properly during lactation and the dry period, no negative effect of rbST or so-called "burn out" occurs.; Dairy Day, 1995, Kansas State University, Manhattan, KS, 1995;
Keywords: Dairy Day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-106-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 742; Recombinant bovine somatotropin; Born out; Sophomore slump